Cubic carbon quantum dots for light-harvesters in mesoscopic solar cells. (10th June 2018) - Dou, Dawei; Duan, Jialong; Zhao, Yuanyuan; He, Benlin; Tang, Qunwei
Abstract: Carbon quantum dots (CQDs) are a new class of carbon nanomaterials that have emerged recently and have garnered much interest in many fields. We present here a simple hydrothermal conversion from Gelidium amansii powders, a type of red algae, to cubic carbon quantum dots (CCQDs). The synthesized CCQDs exist in average size of 4.87 nm, and have fluorescence quantum yield of 3.12% as well as good water solubility. CCQDs are applied as light-harvesters for mesoscopic solar cells. The solar cell tailored with CCQDs/N719 yields a maximized power conversion efficiency of 8.68% in comparison to 7.83% for N719-only device. We anticipate that our results will be a vital point for further research, leading to high-performance next-generation solar cell. Graphical abstract: